2011
DOI: 10.1007/s00221-011-2831-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of muscle fatigue on multi-muscle synergies

Abstract: We studied the effects of fatigue of ankle dorsiflexors on multi-muscle synergies defined as co-varied adjustments of elemental variables (M-modes) that stabilize a task related performance variable (trajectory of the center of pressure, COP). M-modes were defined as muscle groups with parallel changes in activation levels. Healthy participants performed voluntary body sway in the anterior-posterior direction while trying to minimize sway in the medio-lateral direction at 0.25, 0.5 and 0.75 Hz. The trials were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 75 publications
(101 reference statements)
5
27
0
Order By: Relevance
“…As in earlier studies (Singh et al, 2010a; Singh & Latash, 2011), we observed disproportionate changes in the two variance components, “good “ (V UCM ) and “bad” (V ORT ) with a larger increase in V UCM . Hence, the adaptive increase in the synergy index to fatigue has been confirmed.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…As in earlier studies (Singh et al, 2010a; Singh & Latash, 2011), we observed disproportionate changes in the two variance components, “good “ (V UCM ) and “bad” (V ORT ) with a larger increase in V UCM . Hence, the adaptive increase in the synergy index to fatigue has been confirmed.…”
Section: Discussionsupporting
confidence: 88%
“…We suggest that this result was a consequence of selecting frequency of force production close to preferred frequency by the subjects. Preferred frequency has been shown to be close to the natural frequency in several studies of movements of body segments (Latash, 1992; Singh & Latash, 2011; Treffner & Turvey, 1993). In isometric force production tasks, the notion of natural frequency is poorly defined.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…As a result, a large increase in ΔV at the upper level of the hierarchy could have a strong negative effect on the synergy stabilizing the VF force at the lower level of the hierarchy. The current results show that the controller in response to fatigue of either the thumb or index finger did not adopt the strategy of increasing the synergy index at the highest level (as could be expected from earlier studies, (Singh & Latash, 2011; Singh et al, 2010b; Singh et al, 2012). …”
Section: Discussionsupporting
confidence: 71%